DOI: 10.29007/8n5b
|View full text |Cite
|
Sign up to set email alerts
|

Joyful Learning Model: Improving Higher Order Thinking Skill and Students' Learning Motivation at Senior High School

Abstract: Higher-Order Thinking Skills (HOTS) is one of the most important aspects to increase the quality of education. However, HOTS in SMA Muhammadiyah 1 Pontianak is considered still not appearing. This can be seen from the practice questions given by the teacher still using the verb C1-C3. Besides that based on the result of interviews with students, the learning pattern applied by biology teachers who still conventional method makes students bored and less motivated to study biology. The use of a joyful learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The result of research by Bhakti et al (2019) concluded that joyful learning can help student to learning easily. That is similar with the result of researh by Ardiyanti et al (2021) about how to implementing joyful learning model to improve higher-order thinking skill and learning outcomes from the students. The research about monopoly learning media that can help teacher to improve learning motivation and outcomes learning of student also can find on research by Putra and Nisa (2021).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The result of research by Bhakti et al (2019) concluded that joyful learning can help student to learning easily. That is similar with the result of researh by Ardiyanti et al (2021) about how to implementing joyful learning model to improve higher-order thinking skill and learning outcomes from the students. The research about monopoly learning media that can help teacher to improve learning motivation and outcomes learning of student also can find on research by Putra and Nisa (2021).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, there is also research that implements joyful learning models using student worksheet (Arianti et al, 2020). Ardiyanti et al (2021) using Likert scale questionnaires for collecting data. Research by Nurhayati et al (2022) about the development of joyful learning models in the implementation of social studies learning in elementary schools.…”
Section: Introductionmentioning
confidence: 99%
“…In school quality planning, religious-based elementary school managers involve school stakeholders through repeated discussions and reviews and end with ratification. The substance contained in the quality planning of religious-based elementary schools is the vision and mission that promotes the quality to be achieved, gap analysis, goals, and targets that lead to efforts to realize school quality (Ardiyanti et al, 2021;Bray et al, 2023;Tafani & Kamaludin, 2023). Goals and programs have quality content, activities supporting quality achievement, and resources (including budgets) that favor quality creation.…”
Section: Quality Planning For Religious-based Elementary Schoolmentioning
confidence: 99%
“…Research results by Ardiyanti et al (2021) revealed that the results obtained from testing show that a fun learning model can increase HOTS and students' learning motivation, indicated by the HOTS effect size value obtained of 0.31, which is included in the medium category, and students' learning motivation with an effect size value of 1.15 which is categorized as very high. In contrast to fun learning, combining technology (Kahoot) to create learning-themed quizzes or games can help teachers provide learning with unique media that students like, thereby making students more interested and more creative in the learning process.…”
Section: Introductionmentioning
confidence: 99%